Anesthetic Propofol Promotes Tumor Metastasis in Lungs via GABAAR‐Dependent TRIM21 Modulation of Src Expression. Issue 18 (15th July 2021) - Liu, Qidong; Sheng, Zhihao; Cheng, Chun; Zheng, Hui; Lanuti, Michael; Liu, Rong; Wang, Ping; Shen, Yuan; Xie, Zhongcong
Abstract: Generation of circulating tumor cells (CTCs), a key step in tumor metastasis, occurs during surgical tumor resection, often performed under general anesthesia. Propofol is the commonly used anesthetic, but its effects on CTCs and tumor metastasis remain largely unknown. Propofol effects are investigated in an experimental metastasis model by injecting tumor cells and, subsequently, low‐ or standard‐dose propofol to nude mice through tail vein. Propofol‐ or vehicle‐treated tumor cells are also injected to the mice. An in vitro tumor cell–vascular endothelial cell adhesion assay, immunofluorescence, and other methods are employed to assess how propofol affects tumor cell adhesion and extension. Propofol induces more lung tumor metastasis in mice than control. Mechanistically, propofol enhances tumor cell adhesion and extension through GABAA R to downregulate TRIM21 expression, leading to upregulation of Src, a protein associated with cell adhesion. These results demonstrate that propofol may promote tumor metastasis through GABAA R–TRIM21–Src mechanism. Abstract : The commonly used anesthetic propofol activates GABA receptors to downregulate expression of TRIM21, a protein mediating tumor metastasis, and consequently to upregulate expression of Src, a protein regulating cell adhesion and extension, leading to the promotion of tumor metastasis in lungs of mice. These data suggest GABA receptor–TRIM21–Src–tumor cell adhesion/extension as the underlying mechanism of tumor metastasis.